2017
DOI: 10.1080/17518253.2017.1342001
|View full text |Cite
|
Sign up to set email alerts
|

Esterification synthesis of ethyl oleate catalyzed by Brønsted acid–surfactant-combined ionic liquid

Abstract: ABSTRACT3-(N,N-dimethyldodecylammonium) propanesulfonic acid hydrogen sulfate [HSO 4 ]), a Brønsted acidic-surfactant-combined ionic liquid, was successfully prepared from cheap materials and applied to catalyze the esterification synthesis of ethyl oleate using oleic acid and ethanol as precursors. The produced condition of oleic acid ethyl ester was optimized including the amount of catalyst, reaction time, molar ratio and content of water. Under optimal condition (ethanol to oleic acid molar ratio, 3:1; amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Anion exchange membranes (AEMs), a kind of ion exchange membrane with selective permeability, have the function of blocking gas, cations, and conducting anions, and can be used in fuel cells, liquid flow cells, and so on . In order to meet the requirements of practical applications, AEMs need to have good ion conductivity, strong mechanical properties, high‐dimensional stability, and other comprehensive performance .…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange membranes (AEMs), a kind of ion exchange membrane with selective permeability, have the function of blocking gas, cations, and conducting anions, and can be used in fuel cells, liquid flow cells, and so on . In order to meet the requirements of practical applications, AEMs need to have good ion conductivity, strong mechanical properties, high‐dimensional stability, and other comprehensive performance .…”
Section: Introductionmentioning
confidence: 99%
“…Using a synergistic effect between 2 fillers can be an efficient way to tackle these problems, as reported in other systems, such as nanomagnetite and carbon nanofiber, CNTs and graphene, and carbon black and CNTs . A compatibilizer has usually been used to improve the compatibility between nanofillers and the polymer matrix, including maleic anhydride grafted HDPE, ethylene‐vinyl acetate (EVA) copolymer, and ethyl oleate . EVA is suitable as a compatibilizer because it is a kind of thermoplastic material that consists of vinyl monomer and vinyl acetate (VA) monomer.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM and FTIR results indicated that the flame‐retardant mechanism of DPPM in RPUF was the forming of intact and continuous char layer on the surface of RPUF in thermal degradation of the composite, which prevented the heat and mass transfer between the gas and the condensed phases and effectively protected the substrate material from burning. These flame retardants can be extended for multifunctional polymer nanocomposites with an aim to broaden the applications of inert polymers especially in the form states in the fields such as electromagnetic interference shielding, energy storage and other sensing applications …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the main flame retardants for RPUF are the halogen‐based compounds such as pentabromodiphenyl ether, chloroethylphosphate, etc, which may endow RPUF excellent flame retardation . However, when burning, such retardants release a lot of toxic gases which pollute environment and damage people's health . Thus, the environmentally‐friendly flame‐retardant additives with good flame retardancy are particularly needed.…”
Section: Introductionmentioning
confidence: 99%